(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This study examines criminal behavior through a psychological lens, analyzing factors that contribute to crime and classifying offenders into profiles such as the sadistic, psychopathic, and pressure-driven types. It explores the link between these profiles and psychological disorders using theories like Freud’s psychoanalysis, social learning theory, and cognitive-behavioral therapy. The paper highlights the role of psychological treatment—such as group therapy and in-prison programs—in reducing recidivism. It also emphasizes the importance of family and societal support during reintegration. Ultimately, the study advocates for a holistic therapeutic approach to understanding and addressing criminal behavior.